Experimental and analytical studies on stability of ultra-strong thin-walled steel tube and coupler scaffolds. (15th January 2023) - Chen, Zhihua; Lv, Jiacheng; Liu, Hongbo; Liu, Qun; Ye, Borui
Highlights: A new ultra-strong thin-walled steel tube and coupler scaffold is developed. Six full-scale UTSTCS specimens were designed and tested. Parametric analysis was performed based on FEM considering semi-rigid behavior. A design method to predict the ultimate bearing capacity of UTSTCSs is proposed. Abstract: In this study, to improve the erection efficiency and reduce the weight of structures, an ultra-strong thin-walled steel tube and coupler scaffold (UTSTCS) is developed and investigated. Notably, the weight of this UTSTCS is ∼60% that of traditional scaffolds. Six ultra-high full-scale UTSTCS specimens are constructed and tested to determine the bearing capacity of the UTSTCS. A finite element model is built considering the initial member imperfection and semi-rigid behavior of right-angle couplers, based on which parametric studies are then conducted to investigate the method for determining the ultimate bearing capacity and influence of various geometric properties on the stability behavior of UTSTCSs. Compared with that of traditional scaffolds, the vertical bearing capacity of UTSTCSs does not decrease appreciably when the weight of the steel tube is reduced by 40%. Under a uniform vertical load, the main failure modes of UTSTCSs are top coupler slipping, top horizontal tube bending, and post bending. The joint type of the upper layer members, story height, and post spacing have evident influences on the bearing capacity. Moreover, the results of the proposed method for predicting the ultimate bearing capacity of UTSTCSs are in good agreement with the numerical simulation and experimental results.